Safety and Observations from a Placebo-Controlled, Crossover Study to Assess Use of Autologous Umbilical Cord Blood Stem Cells to Improve Symptoms in Children with Autism. (6th February 2018) - Chez, Michael; Lepage, Christopher; Parise, Carol; Dang-Chu, Ashley; Hankins, Andrea; Carroll, Michael
Abstract : The aim of this exploratory study was to assess the safety and clinical effects of autologous umbilical cord blood (AUCB) infusion in children with idiopathic autism spectrum disorder (ASD). Twenty-nine children 2 to 6 years of age with a confirmed diagnosis of ASD participated in this randomized, blinded, placebo-controlled, crossover trial. Participants were randomized to receive AUCB or placebo, evaluated at baseline, 12, and 24 weeks, received the opposite infusion, then re-evaluated at the same time points. Evaluations included assessments of safety, Expressive One Word Picture Vocabulary Test, 4th edition, Receptive One Word Picture Vocabulary Test, 4th edition, Clinical Global Impression, Stanford-Binet Fluid Reasoning and Knowledge, and the Vineland Adaptive Behavior and Socialization Subscales. Generalized linear models were used to assess the effects of the response variables at the 12- and 24-week time periods under each condition (AUCB, placebo). There were no serious adverse events. There were trends toward improvement, particularly in socialization, but there were no statistically significant differences for any endpoints. The results of this study suggest that autologous umbilical cord infusions are safe for children with ASD. Tightly controlled trials are necessary to further progress the study of AUCB for autism.